Examining organizational health practices among universities in the central region of Uganda - Farooq, Miiro; Othman, Azam; Nordin, Mohamad Sahari; Ibrahim, Mohd Burhan (Journal of Positive Management, 2018)
This study gives insights on the organizational health practices applied in Ugandan universities of the central region. The paper examined four subdimensions of the construct through the use of the data obtained from eight hundred twenty (N=820) randomly selected sample of volunteers from the six universities that have been in existence for the last fifteen (15) years. The data were gathered using a 25- items adopted and adapted from the previous studies reviewed, a Likert scale ranging from strongly disagree to strongly agree  (1-5) was used based on by Keller and Price conception of the construct. Confirmatory Factor analysis a component of structural equation modelling was employed to analyze the four subdimensions of the construct organizational health. The research findings of the empirical cross section survey reflected that there is a relationship between the four factor subdimensions; culture and climate, control and coordination, innovation/invention and accountability even though they are all distinct in nature. Meanwhile, accountability as one of the construct was eliminated from the results in figure 2 due to lower scores in the average variance explained (AVE). The results further exhibited that the four subdimensions of organizational health are reliable and valid measurements of the construct. The data generated was deemed appropriate for the study since structure equation modelling requires a big sample, and fitted the model due to the fact that all the parameter estimates were met. Lastly, the data was analysed through the use of confirmatory factor analysis and the study findings generated are an extension of the previous study findings since there was no similar study done in Uganda especially on higher education using this methodology. The study has greater implications to managers towards improvement of university staff performance and institutional transformation.